ASSESSING THE EFFECTIVENESS OF INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS (IMCI) IN TREATING DIARRHEA IN TODDLERS - Monica, Sandra Dea; Anggraini, Lili (DPW PPNI Provinsi Jawa Barat, 2024)
Background: Diarrheal disease is characterized by changes in stool consistency, leading to frequent watery stools, and an increase in defecation frequency of more than three times per day. This condition is common in young children and requires effective management to prevent dehydration and other complications. Objective: The aim of this study was to evaluate the effectiveness of the Integrated Management of Childhood Illness (IMCI) protocol in treating diarrhea in toddlers at the Telagasari Health Center. Methods: This was a descriptive-analytic study with a cross-sectional design, involving 32 respondents. The study utilized the Chi-Square test for statistical analysis to determine the relationship between IMCI implementation and the recovery from diarrhea in toddlers. Results: The implementation of the IMCI protocol at Telagasari Health Center was found to be 84.4% effective. After receiving treatment according to IMCI procedures, 81.3% of the toddlers showed recovery from diarrhea. The statistical analysis revealed a significant effect of IMCI application on diarrhea healing, with a P-value = 0.000 (p ≤ 0.05), indicating that the implementation of IMCI significantly contributes to diarrhea recovery in children under five. Conclusion: The study concluded that the IMCI protocol is effective for treating diarrhea in children under five at the Telagasari Health Center. Continued implementation and training on IMCI are recommended to improve child health outcomes in the community.